Intensive removal of signal crayfish (Pacifastacus leniusculus) from rivers increases numbers and taxon richness of macroinvertebrate species - Moorhouse, T; Poole, A; Evans, L; Bradley, D; Macdonald, D (Wiley, 2014)
Invasive species are a major cause of species extinction in freshwater ecosystems, and crayfish species are particularly pervasive. The invasive American signal crayfish Pacifastacus leniusculus has impacts over a range of trophic levels, but particularly on benthic aquatic macroinvertebrates. Our study examined the effect on the macroinvertebrate community of removal trapping of signal crayfish from UK rivers. Crayfish were intensively trapped and removed from two tributaries of the River Thames to test the hypothesis that lowering signal crayfish densities would result in increases in macroinvertebrate numbers and taxon richness. We removed 6181 crayfish over four sessions, resulting in crayfish densities that decreased toward the center of the removal sections. Conversely in control sections (where crayfish were trapped and returned), crayfish density increased toward the center of the section. Macroinvertebrate numbers and taxon richness were inversely correlated with crayfish densities. Multivariate analysis of the abundance of each taxon yielded similar results and indicated that crayfish removals had positive impacts on macroinvertebrate numbers and taxon richness but did not alter the composition of the wider macroinvertebrate community. Synthesis and applications: Our results demonstrate that non‐eradication‐oriented crayfish removal programmes may lead to increases in the total number of macroinvertebrates living in the benthos. This represents the first evidence that removing signal crayfish from riparian systems, at intensities feasible during control attempts or commercial crayfishing, may be beneficial for a range of sympatric aquatic macroinvertebrates.